Cortisol modulates the engagement of multiple memory systems: Exploration of a common NR3C2 polymorphism. (September 2019) - Langer, Katja; Moser, Dirk; Otto, Tobias; Wolf, Oliver T.; Kumsta, Robert
Highlights: Stress exposure has been shown to influence the use of different memory systems. Compared to a control task, individuals in the stress conditions adopted a nondeclarative learning strategy more often. Higher pre-stress cortisol levels favored the adoption of this non-declarative learning strategy. The switch between learning strategies was moderated by common genetic variation of the mineralocorticoid receptor. Abstract: Exposure to acute stress has been shown to result in a shift from declarative toward non-declarative learning, presumably mediated by brain mineralocorticoid receptors (MRs). In this study, we aimed to replicate and extend these findings by investigating the role of stress-associated cortisol secretion on learning behavior. Furthermore, we explored the influence of a well-characterized common single nucleotide polymorphism of the MR gene (rs2070951; minor allele frequency: 49.3%) previously shown to influence MR expression and HPA axis activity. Healthy males (n = 74) were exposed to the Trier Social Stress Test or a control condition prior to performing a probabilistic classification task (Weather Prediction Task). The use of a non-declarative learning strategy continuously increased over the course of the learning task after stress exposure, but leveled in the control condition. The shift toward a non-declarative strategy in the stress group was associated with better learning performance. Higher pre-stress cortisol levels favored the adoption of a non-declarative learning strategy. rs2070951 C/C-carriers in contrast to G-allele carriers exhibited a larger secretion of cortisol under stress. Furthermore, control participants homozygous for the C-allele adopted a non-declarative learning strategy less often than stressed participants, whereas the choice of strategy was independent of stress in G-allele carriers. The failure to switch strategies resulted in poorer performance, suggesting a beneficial effect of stress in dependence of MR variation. Consistent with previous findings, the results provide further support for cortisol as a driving force in coordinating the competition between multiple memory systems under stress.